Pengaruh Penerapan Pembelajaran Scientific Method Terhadap Kemampuan Pemahaman Konseptual Dan Kemandirian Belajar - Hadi Hasan; Aan Hendrayana; Syamsuri (Universitas Swadaya Gunung Djati, 2025)
The objective of this study is to determine the effect of implementing the scientific method on students’ conceptual understanding and learning independence in mathematics. This study employs a quantitative approach with a quasi-experimental design. Using purposive sampling, the sample consisted of 78 students from Grade XI of SMK Negeri 2 Pandeglang majoring in Laboratory Management Analysis (APL), with 36 students in the experimental class and 32 students in the control class. The instruments used in this study were written tests and questionnaires. Data analysis techniques included ANOVA (Analysis of Variance) and MANOVA (Multivariate Analysis of Variance). The results showed that students who were taught using the scientific method had significantly higher conceptual understanding and learning independence (p < 0.05), with a very large effect size (d ≥ 2.00), compared to students who were taught using conventional methods.